2002
DOI: 10.1001/jama.287.14.1807
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hypericum perforatum (St John's Wort) in Major Depressive Disorder

Abstract: This study fails to support the efficacy of H perforatum in moderately severe major depression. The result may be due to low assay sensitivity of the trial, but the complete absence of trends suggestive of efficacy for H perforatum is noteworthy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…In other words, all arms - Hypericum, Sertraline, and placebo - improved statistically to the same degree. When this study was published in JAMA [10], most of the press reported (inaccurately) that Hypericum had been proven by the NIH not to work [11]. Sales of Hypericum dropped.…”
Section: The Battle Over Sciencementioning
confidence: 99%
“…In other words, all arms - Hypericum, Sertraline, and placebo - improved statistically to the same degree. When this study was published in JAMA [10], most of the press reported (inaccurately) that Hypericum had been proven by the NIH not to work [11]. Sales of Hypericum dropped.…”
Section: The Battle Over Sciencementioning
confidence: 99%
“…The Hypericum Depression Trial Study Group (HDTSG) [19]conducted a double-blind, randomized trial comparing St. John’s wort (Hypericum perforatum) , sertraline, or inert pill placebo in the treatment of 340 outpatients with major depression. Sertraline and St. John’s wort were not significantly different from placebo in changes on the HAMD by 8 weeks, nor did the two active conditions differ from placebo in rates of full responders.…”
Section: Placebo Response In Antidepressant Trialsmentioning
confidence: 99%
“…The HDTSG [19]trial holds important implications for pharmacotherapy research in depression. The study emphasizes the importance of including both active and inactive comparison treatments when testing antidepressants.…”
Section: Placebo Response In Antidepressant Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the very least the third of patients recruited from primary care should have been offered the option of a wait and see or a placebo option. For an example of the importance of this, see an April 2002 JAMA study9 which compared the effectiveness of sertraline, St John’s wort and a placebo in depressed patients. In this study, the placebo-treated patients had a 31.9% rate of remission of symptoms—about the same as with citalopram in level one of STAR*D. (Also interestingly, the criterion for inclusion in the JAMA study was a HAMDRS score of 20 or higher, while in STAR*D it was only 14 or higher).…”
Section: The Absence Of a “Placebo”mentioning
confidence: 99%